PENGARUH PROMOSI, PREMI DAN PENANGANAN KLAIM TERHADAP TINGKAT PENJUALAN POLIS ASURANSI KENDARAAN PADA PT. ASURANSI STACO MANDIRI CABANG DENPASAR - Ida Bagus Ngurah Wimpascima; Khusnul Khotimah (Forum Manajemen, 2020)
This study aims to analyze and test the effect of the variables examined in this study, namely the Effect of Promotion, Premium and Handling of Claims on the Level of Vehicle Insurance Policy Sales at PT. Staco Mandiri Insurance Denpasar Branch. Data analysis techniques in this study were the validity test, reliability test, data normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, f test, t test and coefficient of determination. The results of this study indicate that partially the promotion, premium and claim handling variables have a positive and significant effect on the level of sales of PT. Staco Mandiri Insurance Denpasar Branch. Simultaneously the promotion variables, premiums and confectionary claims have a positive and significant effect on the level of sales of PT. Staco Mandiri Insurance Denpasar Branch.